Intraoperative margin assessment techniques in breast-conserving surgery: current status and advances - JIN Xiaoding, ZOU Qiang, JIN Yiting (Waike lilun yu shijian)
In breast-conserving surgery, timely and accurate intraoperative margin assessment is crucial for ensuring surgical success and reducing local recurrence rates. This review first outlined the current methods for intraoperative margin evaluation, including rapid pathological examination and specimen imaging techniques. According to the technical classification, this review systematically introduced emerging technologies that have advanced significantly in recent years, encompassing advanced microscopy, advancements in conventional imaging technologies, novel imaging technologies, and techniques based on biochemical and electrical property contrasts of tissues. Finally, the review summarized and compared these technologies horizontally, and proposed several assessment dimensions aligned with surgical clinical needs, aiming to support the optimization and clinical translation of intraoperative margin assessment techniques. Despite the vigorous development of new technologies, further clinical research and technical refinement remain necessary to achieve continuous improvement and innovation, ultimately providing better options for the patients.